2017
DOI: 10.1097/ccm.0000000000002500
|View full text |Cite
|
Sign up to set email alerts
|

Single-Operator Ultrasound-Guided Central Venous Catheter Insertion Verifies Proper Tip Placement*

Abstract: A single-operator ultrasound-guided central venous catheter insertion is effective in verifying proper tip placement and shortens time to catheter utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
0
24
0
3
Order By: Relevance
“…This new method is based on our cumulative experience, with point-of-care ultrasound (POCUS)guided central line tip localization. 5 The study was approved by the appropriate institutional review board (IRB), and requirement for written informed consent was waived by the IRB. All patients were treated in the Medical Intensive Care Unit at Soroka Medical Center, a 1000-bed universityaffiliated, tertiary referral center in southern Israel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This new method is based on our cumulative experience, with point-of-care ultrasound (POCUS)guided central line tip localization. 5 The study was approved by the appropriate institutional review board (IRB), and requirement for written informed consent was waived by the IRB. All patients were treated in the Medical Intensive Care Unit at Soroka Medical Center, a 1000-bed universityaffiliated, tertiary referral center in southern Israel.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that real-time single operator focused cardiac ultrasound during central venous catheter (CVC) insertion is effective in verifying proper tip placement. 5 In this report, we propose that a similar technique can be effectively and safely used for real-time localization of VV-ECMO cannulas.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be executed with 1 operator who is experienced with FoCUS. 52 While this technique requires more expertise, we believe that it is the best real-time verification of the wire in the venous system prior to vessel dilatation. This technique is also attractive for the landmark SCV cannulation technique since it helps remove the uncertainty inherent in this blind procedure.…”
Section: Guidewire Localization By Focused Cardiac Ultrasoundmentioning
confidence: 99%
“…26,[45][46][47] Ultrasound may prevent such inadvertent arterial dilatation and catheterization 47 by visualization of the guidewire within the vein, visualization within the brachiocephalic trunk, 48 or visualization of guidewire in the SVC, RA, or IVC. [49][50][51][52] Reducing complications…”
Section: Confirmation Of Venous Catheterization and Catheter Tip Posimentioning
confidence: 99%
See 1 more Smart Citation